PERUMUSAN MUATAN MATERI AJAR MENGGAMBAR SKETSA BERBASIS PJBL BERORIENTASI ISU KEBENCANAAN BAGI MAHASISWA - Muslim; Adina Sastra Sembiring; Raden Burhan Surya Natadiningrat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Sketching is a fundamental competency that must be mastered by students in Art Education programs, as it functions as a medium for visual thinking, critical observation, and the development of artistic ideas. However, sketching instruction in higher education tends to focus primarily on technical aspects and has not sufficiently integrated real-world contexts, particularly social and disaster-related issues. This study aims to design instructional content for sketching courses based on Project-Based Learning (PjBL) oriented toward disaster-related themes for Art Education students. This study employed a qualitative approach using a literature review method. The research procedures included collecting relevant literature on sketching instruction, the PjBL model, and disaster education; conducting conceptual analysis; formulating learning outcomes; developing instructional content structure; and designing material descriptions, project activities, and assessment strategies. Data were obtained through document analysis and examined using descriptive qualitative techniques. The results indicate that the instructional content design was systematically organized into eight chapters: introduction, basic concepts of sketching, single-object sketching, sketching techniques and media, sketching as a visual thinking process, PjBL-based learning, disaster-oriented sketching projects, and assessment and reflection. The design integrates conceptual understanding, technical skills, visual thinking abilities, and contextual project implementation focusing on disaster-related issues. In conclusion, the PjBL-based instructional content design oriented toward disaster- related themes is considered relevant for enhancing students’ sketching skills, creativity, and social awareness of disaster phenomena. This design is expected to serve as an innovative alternative for developing contextual and meaningful art education learning in higher education.